2021
DOI: 10.3390/molecules26154670
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarbon-Based Flame Retardant Polymer Nanocomposites

Abstract: In recent years, nanocarbon materials have attracted the interest of researchers due to their excellent properties. Nanocarbon-based flame retardant polymer composites have enhanced thermal stability and mechanical properties compared with traditional flame retardant composites. In this article, the unique structural features of nanocarbon-based materials and their use in flame retardant polymeric materials are initially introduced. Afterwards, the flame retardant mechanism of nanocarbon materials is described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 109 publications
(128 reference statements)
1
17
0
Order By: Relevance
“…Carbon nanotubes often require functional modification to reduce agglomeration. [141][142][143] Gu et al 112 prepared core-shell particles (MWCNT-DOPO-OH) based on multi-walled carbon nanotubes and added them to the aluminum hypophosphite (AHP)/PLA system (Figure 4C). The AHP/PLA composite with 15 wt% AHP only reached UL 94 V-2 rating, while with 1 wt % MWCNT-DOPO-OH and 14 wt% AHP, PLA samples passed the UL 94 V-0 rating, and the tensile properties were also improved.…”
Section: Nanoparticles Frsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes often require functional modification to reduce agglomeration. [141][142][143] Gu et al 112 prepared core-shell particles (MWCNT-DOPO-OH) based on multi-walled carbon nanotubes and added them to the aluminum hypophosphite (AHP)/PLA system (Figure 4C). The AHP/PLA composite with 15 wt% AHP only reached UL 94 V-2 rating, while with 1 wt % MWCNT-DOPO-OH and 14 wt% AHP, PLA samples passed the UL 94 V-0 rating, and the tensile properties were also improved.…”
Section: Nanoparticles Frsmentioning
confidence: 99%
“…1D nanoscale compounds are widely used in electromagnetics, optics, catalysis and other fields due to their excellent properties, and have recently been added to PLA as FRs. Carbon nanotubes often require functional modification to reduce agglomeration 141–143 . Gu et al 112 prepared core‐shell particles (MWCNT‐DOPO‐OH) based on multi‐walled carbon nanotubes and added them to the aluminum hypophosphite (AHP)/PLA system (Figure 4C).…”
Section: Flame Retardantsmentioning
confidence: 99%
“…Their key functional properties include extremely good electrical and thermal conductivity, electrochemical and thermal stability, and mechanical strength. Recent studies have also shown their high biocompatibility with cells such as osteocytes and neurons and their antimicrobial activity, which greatly enhances their applicability in biomedical sciences [ 7 , 9 , 21 , 22 ].…”
Section: Carbon-based Nanostructuresmentioning
confidence: 99%
“…In turn, 3-D nanostructures are homo- and heterogeneous materials built from monoblocks with nanometer-scale sizes that form common interfaces. Photonic crystals are an example of 3-D structures [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phthalonitriles are used to prepare composite materials and improve material properties. These studies include the addition of polymer matrix, doping of flame retardant, fluorescent sensing, and photosensitizing properties (Madakbaş et al, 2013;Ilyas et al, 2021;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%